(3QSGdI aj GdbghIs - (3TgGH GdOjf CMeO Hf YHO GdMb GdSfHGWi GdTGaYjs
(3ChdgG (B:s
(3SFd GdTjN TgGH GdOjf CMeO Hf YHO GdMb QMeg Gddg HeG UhQJg (B: (3eG bhdce QVi Gddg Yfce hfaY HYdhece GdeSdejf ai TQGH jSehfg GdbghI s
(3BNQgG (B:s
(3hCeG gPg GdgjFI GdELJeGYjI GdJi gi ehLhOg GdBf adGjTcdg eSde ai MQeJge bGdg CMeO Hf YHO GdMb GdSfHGWi cPG fbd ef GdaJGhi dg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs